Effect Analysis of Boiler Feed Water and Exhaust Gas Turbine Generator against Steam Products - M Ihsan Riady; Bazlina Dawami Afrah; Nabilla Tania Rahma; Edda Anastasia Oktawina (Universitas Medan Area, 2024)
The boiler is a tool that functions to produce steam, consisting of two important parts, namely the heating kitchen to produce heat obtained from burning fuel and the proper boiler to convert water into steam. The petrochemical industry, in terms of meeting steam needs, uses supply from the 4003-U waste heat boiler (WHB), namely a boiler that utilizes exhaust gas from a gas turbine generator (GTG). WHB operation uses two sources of heat and fuel, namely exhaust gas from GTG and natural gas. The calculation method used to determine the results of steam products from WHB is the calculation of heat value and efficiency. Based on calculation data for the period 03 October-09 October 2022, efficiency values range from 67-74%. The size of the WHB efficiency is greatly influenced by several factors, namely the quality of the boiler feed water (BFW), the quality of the fuel and heat source, the quality and amount of combustion air and how much heat is lost through the boiler tubes.